PENENTUAN ANGGOTA ASRAMA DENGAN ITERATIVE DICHOMOTISER THREE - Muhammad Hasan; Muliadi Aziz; Dodon T. Nugrahadi (Lambung Mangkurat University, 2016)
Determination of the members of the boarding will done through assessment the criteria for determining the status of the members of the Sorority. This determination is usually consultation between members according to their respective conscience. Therefore, determination of the members of the boarding will done using Iterative Dichomotiser Three by displaying the root criteria so that it becomes a reference node in the assessment of the Member. Determination of the Member of a dormitory with Iterative Dichomotiser Three produce entropy values i.e. (Kitchen 0.121596288; Hall 0.091945213; Bathroom 0.114734253; Living room 0.159141033; Terrace 0.271219296; Manners 0.228396102; Religious 0.217768967; sensitivity 0.339842104; and the money base of 0). The results of calculation of the information gain is generating decision tree with nodes of the criteria each branch. Based on the results that sensitivity of root and the money Base into base of decision tree with reference to the value of the information gain. The result also shows determination of the predictive reports members of the dormitory with Iterative Dichomotiser Three Keywords: Members of the boarding, Iterative Dichomotiser Three, Entropy, lnformation Gain, Decision Tree Penentuan anggota asrama dilakukan melalui penilaian kriteria-kriteria untuk menentukan status anggota asrama. Penentuan ini biasanya melalui musyawarah antar anggota sesuai hati nurani masing-masing. Oleh karena itu, penentuan anggota asrama dilakukan menggunakan Iterative Dichomotiser Three dengan menampilkan root kriteria sehingga menjadi acuan node dalam penilaian anggota asrama. Penentuan anggota asrama dengan Iterative Dichomotiser Three menghasilkan nilai entropy yaitu 0,89357112 dan nilai information gain dari 9 kriteria penilaian anggota asrama yaitu (Dapur 0,121596288; Aula 0,091945213; Kamar Mandi 0,114734253; Ruang Tamu 0,159141033; Teras 0,271219296; Tata Krama 0,228396102; Keagamaan 0,217768967; Kepekaan 0,339842104; dan Uang Pangkal 0). Hasil perhitungan information gain menghasilkan pohon keputusan dengan node-node kriteria tiap cabangnya. Berdasarkan hasil bahwa Kepekaan menjadi root dan Uang Pangkal menjadi pangkal pohon keputusan dengan mengacu pada nilai information gain. Hasilnya juga menampilkan laporan prediksi penentuan anggota asrama dengan Iterative Dichomotiser Three. Kata kunci : Anggota asrama, Iterative Dichomotiser Three, Entropy, lnformation Gain, Pohon Keputusan